(untitled) (Tamaddun, 2020)
Based on the attitude of the learners towards English speaking (Brown, 1993) he said that the learners have negative attitude probably have anxiety in speaking English class. English also is unfamiliar with the learner so that when the teachers give the task through the English communication, almost the learners are speaking by practicing their mother tongue and infrequently practice of English. The study was intended to give a description of the anxiety of the fourth semester students at Health Polytechnics of Makassar in speaking English. The study puts forward two research questions: (1) Whether or not the fourth semester students at Health Polytechnics of Makassar have high or low anxiety towards direct error correction in speaking English? (2) Whether or not the fourth semester students at Health Polytechnics of Makassar have high or low anxiety towards indirect error correction in speaking English?. The study design employed qualitative descriptive method. The population was the fourth semester students at Polytechnic of Makassar. The sample was 50 respondents which were selected based on the random sampling techniques. The data collection was done by distributing the questionnaire which consisted of 20 items to the respondents. The data were analyzed descriptively in percentage and into mean score. The data were followed by interpretation. The data analysis showed; (1) the fourth semester students had very high and high anxiety towards direct error correction in English speaking practice as the aggregate percentage got from strongly agree plus agree was 65 %, undecided was 35 %, and the rest was 2 % disagree, and (2) had very high and high anxiety toward indirect error correction in speaking practice as the aggregate percentage got from strongly agree plus agree was 38 %, undecided was 50 % and rest was 12 % disagree.